Temperature dependent thermal conductivity of magnetocaloric materials: Impact assessment on the performance of active magnetic regenerative refrigerators. (October 2019) - Silva, D.J.; Davarpanah, A.; Amaral, J.S.; Amaral, V.S.
Highlights: Magnetocaloric systems are evaluated for refrigerant T-dependent conductivities. The temperature span and power is affected 15% for changes of conductivity of 50. The impact on longitudinal and axial thermal conduction is discussed. Abstract: Due to the dynamic nature of the active magnetic regenerative mechanism in magnetocaloric refrigeration, the thermal conductivity of the refrigerant is a critical parameter. Experimental studies have shown how the thermal conductivity of high-performance magnetic refrigerants can drastically change around their Curie temperatures ( TC ). However, this fact has been largely ignored in the numerical simulation of devices, raising the need to assess the impact of this approximation, particularly when the simulations are aimed at optimizing or dimensioning a particular device geometry. In this paper we show how, by employing a unidimensional numerical model of a magnetic refrigerator with parallel plates, two different temperature dependent thermal conductivity scenarios of the refrigerant affect the resulting temperature span and cooling power. By considering a gadolinium-like material as the refrigerant with thermal conductivities varying 50% near its TC, a change of the resulting device temperature span of  ∼15% is reached. The cooling power is also affected, changing also  ∼15% when the considered systems are at half their respective maximum temperature span. Our results are also discussed in terms of other geometries where the impact of these effects can be even larger, namely in cases where the axial thermal conduction in the AMR element is not negligible, or the time-scale of longitudinal thermal processes has a larger impact on the optimum operating frequency.